Direct treatment versus indirect: Thermo‐ablative and mild hyperthermia effects. (30th April 2020) - Payne, Macy; Bossmann, Stefan H.; Basel, Matthew T.
Abstract: Hyperthermia is a rapidly growing field in cancer therapy and many advances have been made in understanding and applying the mechanisms of hyperthermia. Secondary effects of hyperthermia have been increasingly recognized as important in therapeutic effects and multiple studies have started to elucidate their implications for treatment. Immune effects have especially been recognized as important in the efficacy of hyperthermia treatment of cancer. Both thermo‐ablative and mild hyperthermia activate the immune system, but mild hyperthermia seems to be more effective at doing so. This may suggest that mild hyperthermia has some advantages over thermo‐ablative hyperthermia and research into immune effects of mild hyperthermia should continue. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Therapeutic Approaches and Drug Discovery > Emerging Technologies Implantable Materials and Surgical Technologies > Nanoscale Tools and Techniques in Surgery Abstract : Hyperthermia permits the systemic treatment of tumors and metastases. Red arrows: negative interactions, green arrows: positive interactions.